Costa Rica and Panama in the Independence: Contacts between the Authorities of Costa Rica and Panama during the Independence from Spain - Sáenz-Carbonell, Jorge Francisco (2021)
The article explains the immediate background of the independence of Costa Rica and Panama from Spain and how they both became independent separately in 1821 and refers to the contacts they maintained in 1822 and 1823. The close trade relationships among the inhabitants of Costa Rica and Panama are mentioned and the effects of the Constitution of Cádiz regarding the new political-administrative division are analyzed. After the independence from Spain, in the case of Costa Rica in October and for Panama in November of 1821, emerged a possibility for both of them to build a new country. Nevertheless, after their independence new hegemonic powers appeared and their presence defined a very different fates for each territory. Despite all this, the trade exchange prevailed and the contact between the highest authorities of Costa Rica and Panama in 1822 and 1823 was friendly.